Alcohol use among restaurant workers: An examination of the impact of work-related stress and workplace culture - Rocheleau, Gregory Christopher (2008)
Despite reports indicating high levels of alcohol use in the restaurant industry, little research has examined alcohol use among restaurant workers in an in depth fashion. Through an examination of personal characteristics, workplace stress, and workplace culture, this study explores the prevalence of alcohol use in the restaurant industry. Twenty restaurant employees were interviewed, recruited via snowball sampling and flyers posted on various college campuses in southeast Michigan. High levels of alcohol use were found to be related to a combination of personal characteristics, workplace stress, and workplace culture. Results supported social learning theory, with heavy drinking being positively and negatively reinforced, having no significant deterrence, and thus established as normative behavior. Findings also suggest that more could be done to curb heavy drinking, particularly with regards to the cultural elements (tolerance for hung-over employees, after-shift drinking, on-the-clock drinking, etc.), implementing drug-testing programs, and providing employees with substance abuse information